2007
DOI: 10.1016/j.cardiores.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C prevents zidovudine-induced NAD(P)H oxidase activation and hypertension in the rat

Abstract: Chronic AZT administration increases blood pressure and promotes cardiovascular damage through a NAD(P)H oxidase-dependent mechanism that involves PKC delta. Vitamin C antagonizes these adverse effects of AZT in the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
2
28
1
Order By: Relevance
“…For example, in rat models of hypertension and renal dysfunction, treatment with vitamins C and E prevented renal inflammation and decreased arterial pressure, thus improving renal function (323). However, vitamin E treatment in hemodialysis patients with chronic kidney disease did not reduce oxidative protein modifications and lipid peroxidation (181), although a reduction in oxidative stress markers (60,185) and improvements in endothelial function (356) inhibition of NADPH oxidase activity (230). In contrast, several clinical trials, such as the long-term trial performed by Sesso et al, have found that vitamins C and E have no preventive effect with regard to cardiovascular events, including coronary revascularization, non-lethal myocardial infarction, stroke, or CVD death (54,178,288).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…For example, in rat models of hypertension and renal dysfunction, treatment with vitamins C and E prevented renal inflammation and decreased arterial pressure, thus improving renal function (323). However, vitamin E treatment in hemodialysis patients with chronic kidney disease did not reduce oxidative protein modifications and lipid peroxidation (181), although a reduction in oxidative stress markers (60,185) and improvements in endothelial function (356) inhibition of NADPH oxidase activity (230). In contrast, several clinical trials, such as the long-term trial performed by Sesso et al, have found that vitamins C and E have no preventive effect with regard to cardiovascular events, including coronary revascularization, non-lethal myocardial infarction, stroke, or CVD death (54,178,288).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…It is probable that the differences in the susceptibility to AZT among different cells accounts for these discrepancies. It is to be recalled that there is evidence that cytotoxic effects of AZT depend on the rise in the ROS production (10,12,(30)(31)(32). Accordingly, the treatment with the anti-oxidant vitamin C is able to prevent AZT-induced toxic lesions in rat cardiomyocytes (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…It is to be recalled that there is evidence that cytotoxic effects of AZT depend on the rise in the ROS production (10,12,(30)(31)(32). Accordingly, the treatment with the anti-oxidant vitamin C is able to prevent AZT-induced toxic lesions in rat cardiomyocytes (10,12). The adrenal gland is one of the organs with the highest concentration of vitamin C in the mammalian body (33), which not only is a cofactor required for both steroid-hormone and catecholamine synthesis, but also prevents the destructive effects of lipid peroxidation on adrenocortical mitochondria cytocrome P450 (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations